Improving reproductive health counseling for women with chronic kidney disease in nephrology settings - Yosin, Esti Pratiwi (Science Midwifery, 2025)
Chronic kidney disease (CKD) presents significant challenges for women of reproductive age, particularly regarding pregnancy planning and maternal-fetal health risks. This study explores the perspectives of women with CKD on pregnancy and family planning, focusing on communication gaps between patients and nephrologists at Murni Teguh Hospital Pematang Siantar. Using a qualitative research design, semi-structured interviews were conducted with 30 women aged 18–45 years diagnosed with CKD at varying stages. Thematic analysis identified three key issues: (1) limited discussions with nephrologists regarding pregnancy and contraception, (2) patient concerns about pregnancy risks, and (3) the need for a multidisciplinary approach in reproductive healthcare. The findings revealed that 73.3% of participants had never received preconception counseling, despite expressing significant concerns about CKD-related pregnancy complications. Many participants perceived pregnancy as a high-risk endeavor due to fears of worsening renal function, hypertensive disorders, and adverse fetal outcomes. The study further highlights the critical role of nephrologists in reproductive health counseling, emphasizing the need for integrated care involving obstetricians and reproductive specialists. Enhancing nephrology training programs, implementing standardized reproductive health counseling protocols, and fostering patient-centered communication are essential for improving pregnancy outcomes among women with CKD. Future research should explore interdisciplinary interventions aimed at addressing the systemic barriers to reproductive health discussions in nephrology care.